Reflections and perspectives for constituting the identity of students in Youth and Adult Education (Research, Society and Development, 2020)
This paper presents an excerpt from a research developed in the Degree Course in Natural Sciences, at the Federal University of Pampa - Campus Dom Pedrito, on identity construction of students in Youth and Adult Education (YAE). It was aimed to figure out both YAE student life stories and their process of identity construction and reconstruction. Methodologically it was characterized as a case study, with an exploratory/explanatory character and a qualitative approach. It had as locus the Supervised Internship in high school, and was carried out in a public educational institution of a municipality in the region of Campanha from Rio Grande do Sul State, Brazil. The research subjects were the 25 students from the Totality Nine of YAE. It was found that the majority were under 35 years old, pursuing the modality in search of insertion in the labor market or to improve employment, dream of going to university and attribute to the family a strong social bond. It was concluded that the speeches of YAE students represented in the texts express understanding about themselves, of others about them, and expectations about the future, being both, school and YAE, a strong divider between past and future.